SILICATE MELTS: THE ANOMALOUS PRESSURE DEPENDENCE OF THE VISCOSITY - Bottinga Y.; Richet P. (My University, 1995)
The decrease of the specific volume, when the extent of polymerization diminishes, is a cause of the pressure sensitivity of the viscosity of silicate melts. This effect can be explained by means of the Adam and Gibbs (1965) theory, taking into account the pressure dependence of the degree of polymerization of the melt and its influence on the configurational entropy. At temperatures close to their glass transitions, liquid silica and SiO2-Na2O melts have configurational entropies that are probably due to the mixing of their bridging and nonbridging oxygen atoms.